2019
DOI: 10.1177/0300060519867832
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for burnout among chemistry education undergraduates in Nigeria

Abstract: The aim of this study was to determine how effectively rational emotive behavior therapy (REBT) could help university undergraduate students in chemistry to manage academic burnout. Methods: We surveyed 468 undergraduates in the chemistry education program for eligibility and included the first 30 students who showed symptoms of high burnout. We randomly assigned 15 students each to the experimental and control groups. The Oldenburg Burnout Inventory for college students was used to assess students' burnout at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…[44] Some similar studies with adequate sample sizes based on power calculations include that of Ogbuanya et al (n = 124) [8] , Ugwoke et al (n = 54) [37] , Ezenwaji et al (n = 52), [38] Igbokwe et al (n = 96), [39] and Ezeudu et al (n = 30, n = 36). [41,42] However, a critical analysis of the sample size utilized in these previous and recent studies shows that our current sample is even larger in size, thus, this is an improvement to the sample sizes utilized by clinical trials investigating the impact of REBT on burnout symptoms.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[44] Some similar studies with adequate sample sizes based on power calculations include that of Ogbuanya et al (n = 124) [8] , Ugwoke et al (n = 54) [37] , Ezenwaji et al (n = 52), [38] Igbokwe et al (n = 96), [39] and Ezeudu et al (n = 30, n = 36). [41,42] However, a critical analysis of the sample size utilized in these previous and recent studies shows that our current sample is even larger in size, thus, this is an improvement to the sample sizes utilized by clinical trials investigating the impact of REBT on burnout symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…Some of the previous researches which examined the impact of REBT on burnout were conducted using only school teachers, [37] English education students, [39] and students of Chemistry education. [41,42]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogbueghu et al (2019) revealed that burnout is common among undergraduate students of Economics Education. Ezeudu, et al (2019) reported that academic burnout is common among undergraduate students of Chemistry Education. Nowack andHanson (2003), andMcCarthy, Pretty andCatano (2006) revealed that burnout poorly forecasts academic achievement of higher institution students.…”
Section: Discussionmentioning
confidence: 99%
“…Carlotto and Camara (2006) added that students' burnout comprises of psychological tiredness and disengagement. Ezeudu et al (2019) suggested that burnout among students need serious intervention. Their report may not only be important to chemistry students but also special education students.…”
Section: Introductionmentioning
confidence: 99%